Analysis of The Effect of Liquidity Ratios, Solvency and Profitability on The Company's Financial Performance - Wuryanti, Lestari; Rosalia, Olyvia; Firayani (Maneggio, 2025)
This study aims to analyze the effect of liquidity, solvency, and profitability ratios on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Financial performance is measured using Return on Equity (ROE) as the dependent variable, while the independent variables consist of the Current Ratio (CR) as a liquidity indicator, the Debt to Equity Ratio (DER) as a solvency indicator, and Return on Assets (ROA) as a profitability indicator. The research method used is a quantitative approach with multiple linear regression analysis, using SPSS software. The results indicate that simultaneously, the three financial ratios significantly affect ROE. Partially, ROA has a significant positive effect on ROE, DER has a significant negative effect, while CR has no significant effect. These findings indicate that profitability is the dominant factor in improving a company's financial performance, while an unbalanced debt structure tends to lower performance. Therefore, companies need to balance asset utilization efficiency and debt management to sustainably enhance firm value.